Explosive Legs Power between Tharu and Non-Tharu Madheshi Girls in the Madhesh Pradesh of Nepal: A Comparative Analysis - Shahi, Suresh Jang (Interdisciplinary Research in Education, 2022)
The paper deals with the objective, which was to compare and analyze the explosive legs power among the girl students of Tharu ethnic and non-Tharu Madheshi girl students in the Madhesh province of Nepal. Also, hypothesized that there is significant difference in explosive legs power between them. It was based on quantitative with comparative design. Altogether 62 girl students have designated as respondents, 31 girl respondents taken from Tharu ethnic and 31 from non-Tharu Madheshi girls. Respondents were taken through multistage sampling method. The standing broad jump test item of AAHPER youth fitness test applied as tool for this study. The standing broad jump test applied to measure the explosive legs power. While comparing the mean score of non-Tharu Madheshi girls, Tharu ethnic girls were found better in explosive legs power. Likewise, p-value of t-test has applied at 0.01 significant level. It has found significant difference between them in explosive legs power of standing broad jump test. Hence, this research paper is found the significant difference between Tharu ethnic and non-Tharu girl students. Therefore, hypothesis (H1) is accepted. In compared on standing broad jump test the non-Tharu girls, Tharu ethnic girls have more participated in intramural-extramural sports tournaments, sporting events as well as physical work.